Clinical observation of a modified technique for intrascleral fixation of flanged three-piece foldable intraocular lenses through a Hoffman pocket - Ye, Hongfei; Wu, Mengxiao; Sun, Wan; Lyu, Jiao; Xu, Yu; Fei, Ping; Peng, Jie; Jin, Haiying; Zhao, Peiquan (Frontiers in Medicine, 2024)
Purpose: To present the observation outcomes of a new technique for intrascleral fixation of a flanged three-piece foldable intraocular lens (IOL) without a conjunctival incision.We retrospectively reviewed a consecutive series of 12 eyes of 12 patients who underwent scleral IOL fixation using this technique.The follow-up period ranged 3 to 12 months. There was a significant improvement in bestcorrected visual acuity, from 0.8 (1.6) logarithm of the minimum angle of resolution (logMAR) preoperatively to 0.45 (0.8) logMAR at the final postoperative follow-up (P=0.012). Notable complications included one case of pupillary IOL capture and increased intraocular pressure.Our novel technique is a viable solution for managing secondary IOL fixation, enabling the use of a wider variety of IOLs and simplifying the repositioning process for dislocated three-piece IOLs. This approach has the potential to lower complication rates and enhance patient recovery.